When indicators fail electricity policies: Pitfalls of the EU's retail energy market Barrier Index. (June 2022) - Almeida, Lucila de; Esposito, Fabrizio; van Zeben, Josephine
Abstract: An important goal of EU energy policy is to ensure energy justice during the green transition. The Commission considers the functioning and competitiveness of the retail energy market for households to be proxies for justice and consumer welfare. The European Barriers in Retail Energy Market Project (the EB Project) is instrumental in assessing and ensuring this competitiveness. The EB Project centres on the creation of the Barrier Index (BI), which identifies barriers to entry in the national markets for electricity and gas suppliers across the EU and ranks Member States on the basis of eight indicators. This article critically assesses the reliability of the BI. A faulty BI could lead Member States down the wrong path or towards bad decisions with respect to the regulation of the retail energy market in light of the EU's policy goals. This research identifies problems with the methodology and data collection regarding the construction of the BI indicators in the electricity market specifically. The latter is exemplified through case studies of the Dutch and Portuguese national reports. The identified issues call into question the reliability of the BI as a whole. Possible measures to improve the quality of indicators are discussed in the conclusions. Highlights: Barrier Index (BI) diverges from indexes based on the HHI in significant ways. The BI is obscure about the methodology used to identify indicators. National reports of the Netherlands and Portugal show omissions and inaccuracies. These findings justify extreme caution in using the BI for shaping policy. Indicator builders should be liable for data misrepresentation used in indicators.